Characterizing population exposure to coal emissions sources in the United States using the HyADS model. (15th April 2019) - Henneman, Lucas R.F.; Choirat, Christine; Ivey, Cesunica; Cummiskey, Kevin; Zigler, Corwin M.
Abstract: In anticipation of the expanding appreciation for air quality models in health outcomes studies, we develop and evaluate a reduced-complexity model for pollution transport that intentionally sacrifices some of the sophistication of full-scale chemical transport models in order to support applicability to a wider range of health studies. Specifically, we introduce the HYSPLIT average dispersion model, HyADS, which combines the HYSPLIT trajectory dispersion model with modern advances in parallel computing to estimate ZIP code level exposure to emissions from individual coal-powered electricity generating units in the United States. Importantly, the method is not designed to reproduce ambient concentrations of any particular air pollutant; rather, the primary goal is to characterize each ZIP code's exposure to these coal power plants specifically. We show adequate performance towards this goal against observed annual average air pollutant concentrations (nationwide Pearson correlations of 0.88 and 0.73 with SO 4 2 − and PM 2.5, respectively) and coal-combustion impacts simulated with a full-scale chemical transport model and adjusted to observations using a hybrid direct sensitivities approach (correlation of 0.90). We proceed to provide multiple examples of HyADS's single-source applicability, including to show that 22% of the population-weighted coal exposure comes from 30 coal-powered electricity generating units. Highlights: New HyADS model quantifies spatial impacts of emissions from hundreds of individual sources. Applicable to many sources, spatial domains, periods, and counterfactual scenarios. National and regional agreement with chemical transport model-based approach.